Komunikasi Wali Murid Dalam Meningkatkan Etika Anak Di PAUD Widya Kumara Desa Karang Bongkot Kecamatan Labuapi Kabupaten Lombok Barat - Ni Luh Aryani (Sadharananikarana: Jurnal Ilmiah Komunikasi Hindu, 2019)
The process of development and formation of child ethics requires good communication between parents and children, between guardians of students and teachers and managers. Reality in the field, especially the communication of student guardians in Paud Widya Kumara, is very less good than communication and support from the guardians of the students, Sehigga encountered problems namely the formation, role and impact of child ethics in Widya Kumara ECD. This research is a descriptive study with a qualitative approach. The data collection technique uses observation techniques, interview techniques, and documentation studies. Based on the results of data analysis conducted it can be concluded that the form of guardian communication in Widya Kumara ECD is based on authoritative type, namely: parents in educating and guiding by involving children fully, so that children become independent and confident, and authoritarian types namely : as a parent of this type always demands and controls his child, because he feels he has power to his child, so that the child becomes less independent, and has less sense of responsibility. This has a positive and negative impact. Form of teacher communication using Authoritative type and Patient that is a teacher in educating and guiding children with Tri Rich Parisudha, Chess Teacher, Tattwam Asi and Mutual Compassion, Sharpening and Fostering, So the role of guardian students in understanding family education first and foremost, besides Effective communication support is needed both materially and non-materially and collaborates to supervise and control all activities of children's activities.